Perlindungan Anak Terhadap Kekerasan Seksual Dalam Dunia Pendidikan - Febri, Yebi (CV WAHANA PUBLIKASI, 2024)
Sexual violence against children in educational environments in Indonesia has increased from year to year. Therefore, the study aims to determine the causes of sexual violence and analyze legal protection for children from sexual violence in the world of education based on statutory regulations. The type of research used is normative juridical. The Legislation approach is used to analyze secondary data including primary and secondary materials. Data collection uses library study techniques. The results of the study indicate that the causes of frequent sexual violence in educational environments or schools are 1) internal factors originating from a teacher, student, educational community unit, 2) external factors originating from the social environment, technology. Legislation in terms of protecting children is to provide rights and protection in the 1945 Constitution, to punish perpetrators of sexual violence against children as regulated in the old Criminal Code, the new Criminal Code, and in real form by establishing a Violence Prevention and Handling Team (TPPK) in schools and a TPPK supervisory task force at the regional level.